(untitled) (Journal of Medical & Health Sciences Review, 2025)
The final enzyme of the coagulation cascade is Coagulation Factor XIII (FXIII) that has a direct role in cross-linking fibrin and stabilizing clot. FXIII deficiency, found either congenital or acquired, leads to development of mechanically unstable clots and a bleeding phenotype with a delay or repeat bleeding despite usual routine screening levels of coagulation. Womenorrhagia or heavy menstrual bleeding is also a common although poorly appreciated clinical presentation in females and it usually takes several years before diagnosis. Chronic menstrual blood loss has important nutritional consequences, especially iron homeostasis, and is a major cause of iron deficiency and iron deficiency anemia in the adolescent group and in women of child bearing age. On the other hand, an acquired form of FXIII deficiency can occur as a disease complication often linked with malnutrition such as chronic liver disease and inflammatory disease as well as protein-losing fistulas, thus indicating a two-way interaction between FXIII activity and nutritional wellbeing. The given review summarizes the existing body of evidence regarding the relationship between FXIII deficiency and menorrhagia and nutritional condition with a special focus on pathophysiology, clinical manifestation, diagnostic issues, and treatment planning. Impact of the late value of recognition, mediating impacts of iron deficiency as morbidities, and need of combined hematologic, gynecologic, and nutritional care are emphasized.